RESEARCHING THE TOXICITY OF DIESEL ENGINES EXHAUST GASES AT DEACTIVATING PART OF CYLINDERS - Romaniak, V. I.; Kelemesh, A. O.; Gorbenko, O. V. (Scientific Progress & Innovations, 2019)
Actual directions of structural and technological improvement of machine-tractor means are reduction of fuel consumption and exhaust gases toxicity. One of the most effective measures to reduce fuel consumption and impact on the environment is using a complex method of complete and partial deactivation of part of cylinders when operating an internal combustion engine at idle run and low loads. This method is limited to modern vehicles. However, the complexity of developing and applying technical means for its implementa-tion lies in the differences of operation modes of machine-tractor implements, and the specifics of operating conditions. In the given researches, the development of measures of shutting-down fuel supply and drive of gas-distributing mechanism in D-240 of MTZ-80 tractor engines is presented. For carrying out experimental researches the KI-5543 rolling-brake stand with measuring devices, the D-240 diesel engine of the MTZ-80 tractor, the“Infracar D1” smoke gauge and the “InfraLight 11P” gas analyzer were used. During the exper-imental tests, three characteristic operating modes of the D-240 engine without loading and under loading Ne = 0...35 kW were selected: 1) typical mode of all 4 cylinders’ operation; 2) artificial operation mode, which was formed by deactivating the fuel supply in 2 cylinders of the 4-cylinder engine; 3) artificial opera-tion mode, which was formed by deactivating fuel supply in 2 cylinders and the gas distribution mechanism in 2 cylinders of the 4-cylinder engine. It has been established that shutting down a part of the diesel engine cylinders leads to a decrease in fuel consumption by 25−27 %, on the average, soot and smoke content of the exhaust gases – by 30−35 %, depending on the engine operation mode. The dependences of hour fuel con-sumption, air flow rate, excess air ratio, soot and smoke content of the four-cylinder diesel engine when de-activating part of its cylinders under different loading modes are given.